2021
DOI: 10.1001/jamanetworkopen.2021.1259
|View full text |Cite
|
Sign up to set email alerts
|

Off-label Use of Direct Oral Anticoagulants in Patients Receiving Surgical Mechanical and Bioprosthetic Heart Valves

Abstract: This cohort study assesses direct oral anticoagulant use in patients with surgical prosthetic heart valves in the United States and evaluates differences in preoperative and postoperative profiles in patients discharged while receiving direct oral anticoagulant vs warfarin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 3 publications
1
1
1
1
Order By: Relevance
“…We identified 15,457 people with a code for ever receiving a mechanical heart valve suggesting that not all mechanical valve replacements are explicitly coded in GP records. A US study showed an overall 1% rate of postoperative DOAC prescribing following surgical aortic or mitral valve replacement with mechanical valves between 2014 and 2017, in 18,000 people with comparable sex and age distributions to our study 8 . This is lower than the 6.8% rate observed in this study.…”
Section: Findings In Contextsupporting
confidence: 67%
“…We identified 15,457 people with a code for ever receiving a mechanical heart valve suggesting that not all mechanical valve replacements are explicitly coded in GP records. A US study showed an overall 1% rate of postoperative DOAC prescribing following surgical aortic or mitral valve replacement with mechanical valves between 2014 and 2017, in 18,000 people with comparable sex and age distributions to our study 8 . This is lower than the 6.8% rate observed in this study.…”
Section: Findings In Contextsupporting
confidence: 67%
“…We identified 15,457 people with a code for ever receiving a mechanical heart valve suggesting that not all mechanical valve replacements are explicitly coded in GP records. A US study showed an overall 1% rate of postoperative DOAC prescribing following surgical aortic or mitral valve replacement with mechanical valves between 2014 and 2017, in 18,000 people with comparable sex and age distributions to our study (5). This is lower than the 6.8% rate observed in this study.…”
Section: Findings In Contextcontrasting
confidence: 64%
“…Furthermore, another registry study was conducted using data from 2014 to 2017 of 177 915 patients after a surgically placed mechanical or bioprosthetic valve. 50 Of patients discharged on a DOAC (type unspecified), 5% had a bioprosthetic valve and 1% had a mechanical valve. There is an increasing usage of DOACs in mechanical valves, even though there is a direct contraindication (dabigatran) or strong precaution against use (rivaroxaban, apixaban, edoxaban) in this population.…”
Section: Discussionmentioning
confidence: 99%